The Development of Techna: Web-Based Online Computer Repairing Service Platform - Azman, Fikri Arif; Darman, Rozanawati (Applied Information Technology And Computer Science, 2021)
Web-based online computer repairing service platform is a website for any technicians at Johor to make their business computer repairing online. The problem faced by traditional computer repairing is that it requires a physical appointment to make the repairs. Hence, the distance and time is needed to be considered here since the customer needs to approach to the technician’s place first for the approval from the technician’s skillset regarding their computer issues. The objective of this project is to develop a website that act as a platform for technicians and customers to do their online appointments instantly based on their nearby location. There are two users are using the client website and that is the technicians and customers who seeks computer repairing service. The visitor of this website can use this system to make their appointment on their issues of their laptop. The answers will be displayed at the nearest technician’s dashboard as their job opportunity. If any technician is interested, the platform will redirect them to the customer’s message for proceeding the repairing process. This website will be built using HTML, CSS, JavaScript and PHP language. The method that this project use is called prototype methodology. The phases are initial plan, construct prototype, customer validation, iterate prototype, repeat the phases until there is no more iteration and finally publish the website. We inject a Geolocation API to the website to get precise location of the user and the technicians, helps the coding to get precise results. In conclusion, Techna is a web-based computer repairing service platform is an online website that offers a platform for technicians and customers to do computer repairing services based on their nearby location.